The Econometric Model of Enterprise Breakups - Anton Abdulbasah Kamil (Program Studi Statistika Unisba, 2010)
we present the model that describes the process of enterprise breakups. We carried out regressionanalyses relating several common measures of performance to standard explanatory variables and avariable measuring the importance of the spun off unit in the master enterprise.